2020
DOI: 10.3390/sym12010181
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Creation and Usage of 3D Model of Structures and Theirs Possible Solution

Abstract: This article describes problems that occur when creating three-dimensional (3D) building models. The first problem is geometric accuracy; the next is the quality of visualization of the resulting model. The main cause of this situation is that current Computer-Aided Design (CAD) software does not have sufficient means to precision mapping the measured data of a given object in field. Therefore the process of 3D model creation is mainly a relatively high proportion of manual work when connecting individual poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…It is shown that current software systems are not yet able to capture geometric shapes in real space with 100% accuracy. This fact was confirmed by the results in [65]. Further inaccuracies may result from the exchange formats used, as confirmed by the experience of [57].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It is shown that current software systems are not yet able to capture geometric shapes in real space with 100% accuracy. This fact was confirmed by the results in [65]. Further inaccuracies may result from the exchange formats used, as confirmed by the experience of [57].…”
Section: Discussionsupporting
confidence: 69%
“…Similar issues are addressed in [64]. The work [65] deals with the same topic in the context of GIS.…”
Section: Cartographic Symbols Used For Special Railway Objectsmentioning
confidence: 86%
“…Due to advances in the processing techniques of digital photogrammetry and computer vision, results comparable to LiDAR can be achieved under specific circumstances, i.e., capturing 3D data with great precision and high quality [1]. The large number of publications in the last five years using point clouds calculated with image-based 3D reconstruction to analyse and monitor objects and surfaces, for example building structures [2][3][4][5] or natural surfaces [6][7][8][9][10], confirm the popularisation of the use of this technique [11].…”
Section: Introductionmentioning
confidence: 99%
“…There are also issues in constructing 3D models themselves [19]. For example, originally, we intended to use two cylinders and a UV sphere to construct each single phospholipid to create a phospholipid bilayer model for the action potential demonstration, but there is a gap in the connection of the cylinder and the UV sphere.…”
Section: Challengementioning
confidence: 99%